HOW DO TRAVEL APPS AFFECT STUDENT’S VISIT EXPERIENCE AND PLACE ATTACHMENT IN LOCAL TRAVEL? THE MODERATING ROLE OF UNIVERSITY IMAGE (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
The lockdown of the COVID-19 pandemic has stimulated local travel activities, and college students have become the main tourists in this kind of tourism. As newcomers to the home city of the university, students may show more curiosity about exploring and learning the new living environment. College students may cultivate a strong attachment to their university when they have learnt in depth about their new living home. Lockdown at home has aroused students’ desire and need to travel, and offered these potential tourists sufficient time to plan their trip via mobile travel apps. Therefore, this study investigated the relationship between college student’s using behavior of travel apps and the place attachment in the home city to their university. Present, tourists have become to enjoy planning and designing their trip by themselves, and travel apps are expected to offer more fun when offering information. Perceived enjoyment was thus adopted as an external variable, and the image of university was adopted as a moderating factor in the extended TAM model. Regarding that Macau is a famous destination with historical heritage and owns several international universities, a survey was conducted with a valid sample of 153 college students studying in Macau. Results showed that perceived usefulness and perceived enjoyment mediate the relationship between ease of use and visit experience. Student’s visit experience has a significant effect on place attachment of the city where their universities are located. And image of university moderated the relationship between visit experience and place attachment. This study contributed to discovering the psychological influence of mobile technology on the new generation of college students. Practical implications and limitations are discussed accordingly.
Keywords: travel apps; place attachment; TAM; college student; Macau